2012
DOI: 10.1155/2012/972562
|View full text |Cite
|
Sign up to set email alerts
|

Placental Amino Acids Transport in Intrauterine Growth Restriction

Abstract: The placenta represents a key organ for fetal growth as it acts as an interface between mother and fetus, regulating the fetal-maternal exchange of nutrients, gases, and waste products. During pregnancy, amino acids represent one of the major nutrients for fetal life, and both maternal and fetal concentrations are significantly different in pregnancies with intrauterine growth restriction when compared to uncomplicated pregnancies. The transport of amino acids across the placenta is a complex process that incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 47 publications
4
50
1
5
Order By: Relevance
“…These lower concentrations of 5-HT in SGA piglets might be attributed to a fall in the number of platelets, as already described in low birth weight infants (Christensen et al, 2006). Another study in foetal piglets also described lower foetal tryptophan concentrations in IUGR (Lin et al, 2012) and suggested this might be because of impaired amino acid transport through the placenta (Avagliano et al, 2012). Although the previous proposition correlates with our data describing lower total tryptophan levels in SGA piglets, we cannot rule out that this latter finding is owing to a lower feed intake in these piglets (Devillers et al, 2007).…”
Section: Discussionsupporting
confidence: 63%
“…These lower concentrations of 5-HT in SGA piglets might be attributed to a fall in the number of platelets, as already described in low birth weight infants (Christensen et al, 2006). Another study in foetal piglets also described lower foetal tryptophan concentrations in IUGR (Lin et al, 2012) and suggested this might be because of impaired amino acid transport through the placenta (Avagliano et al, 2012). Although the previous proposition correlates with our data describing lower total tryptophan levels in SGA piglets, we cannot rule out that this latter finding is owing to a lower feed intake in these piglets (Devillers et al, 2007).…”
Section: Discussionsupporting
confidence: 63%
“…It is possible that the trophoblast mTOR signaling links maternal nutrient availability to fetal growth by modulating the flux of amino acids across the placenta. [36] and [37].…”
Section: Resultsmentioning
confidence: 99%
“…Amino acids are transferred across the placenta by active transport using a complex system with more than 10 different families of amino acid carriers: systems A, L, yþ, yþL, T, X -AG and ASC (Table 1) [36,37]. These carriers can be classified in two classes: accumulative amino acid transporters (mainly represented by system A and X -AG ) and amino acid exchangers (LAT1, LAT2, yþLAT1, yþLAT2 and ASC) [37].…”
Section: Mechanisms Involved In the Placental Amino Acid Transfermentioning
confidence: 99%
“…Glutamate has been reported to be important for placental and fetal metabolism as it generates NADPH for placental fatty acid steroid synthesis (Moores et al 1994, Vaughn et al 1995. Human intrauterine growth restriction studies are characterised by reduced fetal plasma concentrations of essential amino acids such as valine, leucine, isoleucine and lysine (Cetin et al 1988, Avagliano et al 2012. A reduction in uptake of lysine in the placenta due to reduced system A amino acid transport activity has also been demonstrated in pregnancies complicated by intrauterine growth restriction (Dicke & Henderson 1988, Jansson et al 1998.…”
Section: Accelerated Growth In F2 Blastocystsmentioning
confidence: 99%